A rare case of chronic otitis externa due to Mycobacterium tuberculosis. (August 2017) - DeSimone, Daniel C.; Heaton, Philip R.; Neff, Brian A.; Dao, Linda N.; Wengenack, Nancy L.; Fadel, Hind J.
Abstract: Chronic otitis externa due to Mycobacterium tuberculosis complex is extremely rare and very few cases have been presented in the medical literature. We report here the case of an immunocompetent 68-year-old male with chronic auricular drainage, otalgia, hearing loss, external ear canal and tympanic membrane thickening for 3 years who was ultimately diagnosed with tuberculous chronic otitis externa on biopsy of external auditory canal granulation tissue using molecular diagnostic techniques. Later, sputum cultures were positive for Mycobacterium tuberculosis complex indicating disseminated tuberculosis. However, two plausible explanations could be pulmonary TB that disseminated to the ear canal with evidence of middle and outer otitis, or upper airway/nasopharyngeal involvement with direct extension into the middle and outer ear canals. Although extremely rare, extrapulmonary laryngeal head and neck tuberculosis should be considered in immunocompetent patients who present with chronic otitis without prior known exposure to tuberculosis when they fail standard therapy and in whom no other microbiologic cause can be identified.